Andean Bear Livestock Depredation and Community Perceptions in Northern Ecuador. Issue 2 (3rd March 2016) - Zukowski, Benjamin; Ormsby, Alison
ABSTRACT: Human–carnivore conflicts are a major cause of the decline in global carnivore populations. Since 2009, Andean bear ( Tremarctos ornatus ) depredation incidents in Ecuador's northern Andes cordillera have reached unprecedented levels: more than 320 livestock deaths. The objectives of this article were to: evaluate local perceptions and knowledge of the Andean bear in response to frequent depredation incidents; better understand the cattle-raising culture of the region; and describe noted depredation incidents. Interviews were conducted with 83 participants in three locations within the depredation-conflict zone. Locals knew that pastures near the forest were vulnerable to bear depredation but often had few alternatives to raise cattle. Six depredation incidents were described. An effective management approach should concurrently improve livestock husbandry, track several of the region's bears, develop policies that do not reward compensation but acknowledge depredation incidents, and use education to rectify false perceptions and misinformation of bears in the region.